A Financial Ratio Analysis of Oil and Gas Private Company in Indonesia: Before and After Declining the Oil Production - Wiwiek Mardawiyah Daryanto; Sudarmawan Samidi (International Journal of Business Studies, 2018)
As we know that the oil and gas industry is a huge industry and a big contributor to government revenue. However, a signiicant decline in government revenues from this sector is in 2014 by 14.11% to 4.46% in 2015, and in 2016 the value is not too far from the previous year that is 4.58%. This is due to the decline in world oil prices and also the decline in production of Indonesian private oil and gas companies. The purpose of this study is to analyze the financial performance of Indonesia’s private oil and gas company before and after declining the national oil and gas production. The data were collected from financial report of PT. Medco Internasional, Tbk and divided into two periods. The period before the decline in production from 2011 to 2013, and after the decline in production from 2014 to 2016. Financial ratio analysis (FRA) and paired sample t-test were used to analyze the data. The results show that Indonesia’s private oil and gas company is still in good performance even in one year suffered considerable losses. The value of cash ratio, inventory turnover, and collection period signiicantly different before and after the decline in oil and gas production. The authors believe that findings will be helpful for managers who continuously attempt to explore opportunities to provide a higher return.